Spatial variation in the plasma sheet composition: Dependence on geomagnetic and solar activity. Issue 4 (24th April 2014) - Maggiolo, R.; Kistler, L. M.
Abstract We study the spatial distribution of plasma sheet O+ and H+ ions using data from the COmposition and DIstribution Function (CODIF) instrument on board the Cluster spacecraft from 2001 to 2005. The densities are mapped along magnetic field lines to produce bidimensional density maps at the magnetospheric equatorial plane for various geomagnetic and solar activity levels (represented by the Kp and F10.7 indexes). We analyze the correlation of the O+ and H+ density with Kp and F10.7 in the midtail region at geocentric distances between 15 and 20 RE and in the near‐Earth regions at radial distances between 7 and 8 RE. Near Earth the H+ density slightly increases with Kp and F10.7 while in the midtail region it is not correlated with Kp and F10.7. On the contrary, the amount of O+ ions significantly increases with Kp and F10.7 independently of the region. In the near‐Earth region, the effects of solar EUV and geomagnetic activity on the O+ density are comparable. In the midtail region, the O+ density increases at a lower rate with solar EUV flux but strongly increases with geomagnetic activity although the effect is modulated by the solar EUV flux level. We also evidence a strong increase of the proportion of O+ ions with decreasing geocentric distance below 10 RE. These results confirm the direct entry of O+ ions into the near‐Earth plasma sheet and suggest that both energetic outflows from the auroral zone and cold outflow from the high‐latitude ionosphere may contribute to feed the near‐Earth plasma sheet with ionospheric ions.